Sun Tzu in the Age of Autonomous Warfare: A Reinterpretation of Classical Strategy in the Landscape of Cyber and Autonomous Conflict - Turnip, Hiras M. S. (Department of International Relations, Universitas Brawijaya, 2025)
The resurgence of classical military strategy amid the rise of digital technologies and autonomous systems calls for a critical reinterpretation of foundational doctrines. This article revisits Sun Tzu’s The Art of War, focusing on three central principles namely deception, intelligence, and indirect strategy, in the context of contemporary conflict marked by cyber operations, artificial intelligence, and non-kinetic warfare. Using a qualitative approach grounded in literature review and theoretical-critical analysis, the study maps how these classical ideas have been transformed within modern digital battlefields, including algorithmic disinformation, predictive intelligence, and infrastructure sabotage. In addition, the study proposes a fourth, contemporary principle rooted in Sun Tzu’s logic of ambiguity: the manipulation of strategic uncertainty in environments shaped by data, digital noise, and algorithmic bias. The findings suggest that Sun Tzu’s principles not only persist but also evolve structurally in response to technological pressures. This research contributes to the modernization of Eastern strategic thought in the face of modern war’s complexity and emphasizes the need to balance classical wisdom with new ethical frameworks in the age of autonomy. It invites readers to reassess enduring strategic values in light of disruptive, rapidly evolving technologies.